2011
DOI: 10.1002/biot.201100191
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the 3‐hydroxyvalerate component in bioplastic PHBV production by Cupriavidus necator

Abstract: In the current context of global warming, the substitution of conventional plastics with bioplastics is a challenge. To take up this challenge, we must meet different technical and economic constraints. In the case of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), the technical properties can be modulated by varying the 3-hydroxyvalerate content. 3-Hydroxyvalerate (3-HV) enhancement is an issue; therefore, simultaneous evaluation of several 3-hydroxyvalerate-enhancing substrates through fractional factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 24 publications
4
17
0
Order By: Relevance
“…Moreover, the volumetric productivity reached 3.9 mg/L/hour, exceeding by 100% the previously reported results [23].…”
Section: Scale-up Of the Optimized Conditionssupporting
confidence: 42%
See 3 more Smart Citations
“…Moreover, the volumetric productivity reached 3.9 mg/L/hour, exceeding by 100% the previously reported results [23].…”
Section: Scale-up Of the Optimized Conditionssupporting
confidence: 42%
“…This allows the volumetric productivity of 3.9 mg/L/hour which is 100% greater than the previous results [23]. This method remains economical, as it uses only 3.5 g/L of carbon substrates for the production of PHBV with high, 80%, 3-HV content comparing to previously reported studies, with 20 g/L of inducing substrates [25,37].…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Previous studies on the L-threonine metabolic pathway have shown that L-threonine dehydratase, encoded by the tdc operon (Hesslinger et al, 1998), as well as phosphotransacetylase and acetate kinase A/propionate kinase II, encoded by the pta and ackA genes, respectively, are involved in the degradation of L-threonine (Van Dyk and LaRossa, 1987). Recently, 2-ketoacids, intermediate metabolites in branched amino acid biosynthesis, have been successfully diverted to form structurally similar, but non-natural, alcohols Berezina, 2012;Mainguet and Liao, 2010;Peralta-Yahya and Keasling, 2010). Among them, 2-ketobutyrate, in particular, has been used as a starting point for the production of 1-butanol and 1-propanol (Shen and Liao, 2008).…”
Section: Introductionmentioning
confidence: 99%